(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
A competency approach in education is another stage in the development of educational quality standards and criteria, which are mainly objective, but not in a subjective way, designed to assess the level of training of a specialist. However, the process of training a specialist also requires certain competencies from the subjects of the educational process, the most important of which is cognitive competence, which determines the relevance of the study